IMPROVING LISTENING COMPREHENSION OF THE SECOND YEAR STUDENTS OF SMA NEGERI I MARAWOLA THROUGH RECORDED DIALOGUES - Nur Syariatin (BABASAL English Education Journal, 2021)
This Research was aimed to prove that the use of recorded dialogues in teaching listening can improve the listening comprehension of the second year students of SMU Negeri I Marawola. This research applied true experimental research design involving two sample groups; experimental and control groups. The sample of this research was 62 second year students of SMU Negeri I Marawola selected with a random sampling technique. The instrument of data collection was a test which was given to the research sample as pretest and posttest. The data gathered were analyzed statistically. The result of the data shows that the t- counted (2.03) was greater than the value of t- table (1.671) by applying 0.05 level of significance and the degree of freedom (df) was 60. It meant that the use of recorded dialogue can significantly improve the listening comprehension of the second year students of SMU Negeri I Marawola. In brief, recorded dialogues were effective to be used to improve listening comprehension.